Solid state physics an introduction to theory - Galsin, Joginder Singh 1947- (Academic Press, 2019)
Solid state physics: an introduction to theory is a foundational textbook on the theory of crystalline solids covering a wide spectrum of topics on solid state physics. The physical concepts involved are presented in an easily comprehensible manner, rendering it appropriate as an introduction to solid state physics for undergraduate/graduate programs in physics, chemistry, engineering, and materials science. Providing basic knowledge on recent topics of interest such as the quantum Hall effect, high temperature superconductivity, and physics of nanomaterials and nanotechnology, the book begins with the description of the structure of crystalline solids in real and reciprocal spaces where the actual interpenetration of simple cubic and hexagonal structures is explicitly depicted in the formation of other structures. A brief account of the types of bonding in solids is also presented. Elastic, thermal, transport, electrical, electronics (especially electronic band structure), semiconducting, dielectric, optical, magnetic, superconducting, and quantum tunneling properties of crystalline solids are addressed in more detail. Further topics such as Fermi surfaces in metals, defects in crystalline solids, amorphous solids, and physics of nanomaterials are also included.